Advancing Environmental Education Practice - Krasny, Marianne E. (Cornell Series in Environmental Education, 2020)
In this important intervention, change-agent Marianne E. Krasny challenges the knowledge-attitudes-behavior pathway that underpins much of environmental education practice; i.e., the assumption that environmental knowledge and attitudes lead to environmental behaviors. Krasny shows that certain types of knowledge are more likely than others to influence behaviors, and that generally it is more effective to work with existing attitudes than to try to change them. The chapters expand the purview of potential outcomes of environmental education beyond knowledge and attitudes to include nature connectedness, sense of place, efficacy, identity, norms, social capital, youth assets, and individual wellbeing. Advancing Environmental Education Practice also shows how, by constructing theories of change for their environmental education programs, environmental educators can target specific intermediate outcomes likely to lead to environmental behaviors and collective action, and plan activities to achieve those intermediate outcomes. In some cases, directly engaging program participants in the desired behavior or collective action can lead to changes in efficacy, sense of place, and other intermediate outcomes, which in turn foster future environmental actions. Finally, Advancing Environmental Education Practice shares twenty-four surveys that assess changes in environmental behaviors and intermediate outcomes, and provides guidelines for qualitative evaluations. Thanks to generous funding from the Cornell Department of Natural Resources, the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellpress.cornell.edu/cornell-open) and other Open Access repositories.